A simple approach on implementing IMU sensor fusion in PID controller for stabilizing quadrotor flight control - Zul Azfar, A.; Hazry, Desa, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/